Decentralized control of two DC microgrids interconnected with tie-line - Adhikari, Sujan (2018)
This paper examines the interconnection of two DC microgrids (MGs) with tie-line. The voltages at respective MG buses are controlled to manage the power flow across the tie-line. Formation of such a DC MG cluster ensures higher reliability of power supply and flexibility to manage distributed energy resources and loads in the system. Two MGs consist of photovoltaic and battery units interfaced by power electronic converters. The bus voltages of two DC MGs act as an indicator for the power flow monitoring the supply-demand balance. A decentralized control approach is proposed to control each MG and bus voltage fluctuation in an allowable range. Furthermore, a mode adaptive decentralized control approach is proposed for seamless mode transition in order to assign microgrid operation modes and for the power management of DC MGs. The effectiveness of the proposed concept is validated by simulation and experimental results.